From Concept to Reality: An Assessment of Gender and Development Awareness and Perception Levels as Basis for Gad Extension Programs - Candida Punla (Indonesian Journal on Education (IJoEd), 2025)
This study examines teachers' awareness and perceptions of Gender and Development (GAD) in DepEd Bataan, specifically in Dinalupihan West District Elementary Schools. To fill a gap in existing survey tools, the researcher developed and validated a new scale with 67 items on awareness and 60 on perceptions. The validation process, including expert feedback and a literature review, showed high item relevance (I-CVI=0.958) and content validity (S-CVI/SU=0.90). Reliability analysis with 75 respondents produced a Cronbach’s Alpha of .943. Findings from 228 teachers highlight a need to enhance GAD awareness, especially regarding gender analysis, laws, and core concepts. The study calls for stronger GAD initiatives in the district to promote a more inclusive and informed educational environment.